An Empirical Exploratory Analysis of Failure Sequences in a Commodity Operating System - dos Santos, Caio Augusto Rodrigues; Matias Jr., Rivalino; Trivedi, Kishor (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2019: Anais do IX Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2019)
A fundamental aspect of software reliability engineering is to comprehend how software systems fail, which means understand the dynamics that govern the different types of failure manifestations. In this paper, we present an exploratory study on multiple-event failures, looking for systematic patterns of sequences of failures in logs of a commodity operating system. This study is based on real failure data collected from hundreds of computers. The major contribution of this work is the method proposed to discover patterns of failure sequences and their attributes, which is generic enough to be applied to any other software systems, with minor changes. The empirical findings of this study include 153 different patterns of OS failure sequences discovered, along with statistical analyses of their properties.